Building Smart LEGO MINDSTORMS EV3 Robots : Leverage the LEGO MINDSTORMS EV3 platform to build and program intelligent robots. - Markland, Kyle (Packt Publishing, 2018)
Chapter 6: Falcon - Remote Control Race Car; Technical requirements; Mechanical design; Drivetrain; Drive motors; Gear ratios; Differential; Final drive ratio; Steering ; Cosmetic design; Sensors; Infrared sensor; Rotation sensor; Programming; Control scheme; MyBlocks; Centering the steering; Saving code as a MyBlock; Steering left; Steering right; Returning the steering to center; Assembling the program; Accessing your MyBlocks; Getting started; Programming the cases; Putting it all together; Summary; Chapter 7: GPS Car - Autonomous EV3 Navigation; Technical requirements; Hardware.